Housing and SDGs in Urban Africa
XIX, 338 p. 44 illus., 31 illus. in color.
Keywords: There is a dearth of collections of scholarly works dedicated wholly to African issues, that comes out of the work done by African scholars and practitioners with both African collaborators and from elsewhere. This volume brings together scholarly works and thoughts that cut across and intertwine the tripods-environment-consciousness, socially just development and African development into options that could deliver on the promise of the SDGs. The book project is an initiative of the Centre for Housing and Sustainable Development at the University of Lagos, which realized the gap in ground research linking the housing sector with the SDGs in African cities. This book therefore presents chapters that explore the interconnections, interactions and linkages between the SDGs and Housing through research, practice, experience, case-studies, desk-based research and other knowledge media.